Improved healing and macrophage polarization in oral ulcers treated with photobiomodulation (PBM). Issue 4 (16th December 2021) - Ryu, Hyun Seok; Lim, Nam Kyu; Padalhin, Andrew Reyes; Abueva, Celine; Park, So Young; Chung, Phil‐sang; Woo, Seung Hoon
Abstract: Objectives: The effect of photobiomodulation (PBM) treatment on wound healing and macrophage polarization was investigated in vivo. Animal models of oral ulcers were simulated through chemically induced oral ulcers in rats. Materials and Methods: PBM treatment using an infrared pulsed laser was used to treat oral ulcers in the animal models. Twelve Sprague–Dawley rats were randomly divided into four groups depending on set absorbed energy: Group 1 (control), Group 2 (30 J), Group 3 (60 J), and Group 4 (100 J). Laser treatment was performed every other day for 8 days after ulcer confirmation. Parameters used were as follows: wavelength 808 nm, power output 50 mW, spot size 10 mm, frequency 10 Hz, and pulse duration 1 millisecond. Ulcers were measured to determine the effect of the treatments over time. Histology, immunostaining, and real‐time polymerase chain reaction analyses were performed to evaluate the effect of PBM treatment on macrophage‐related (IL‐6/IL‐10) and wound‐healing‐related (TNF‐α/TGF‐β/MMP‐2) cytokine expression. Results: Histological examinations indicate that the PBM treatment stimulated a higher level of wound recovery after 8 days of treatment at 60 J absorbed energy compared to other treatment groups. Analyses of relative gene expression of proinflammatory, anti‐inflammatory, and tissue remodeling cytokines indicate that the macrophages in the tissue samples were predominantly characterized as M2 subtypes (alternatively activated), which possibly accounts for the accelerated tissue repair in the animal model of oral ulcer. Conclusion: This preliminary study stands as a proof of concept regarding the potential use of infrared laser PBM treatment for oral ulcers which have not been previously investigated upon. PBM treatment affects macrophage polarization and enhances wound healing. Further experimentation will be conducted to expand the understanding of how PBM treatment affects the healing mechanism of ulcers.